Gender essentialism in Canadian foreign aid commitments to women, peace, and security - Tiessen, Rebecca (International journal (Toronto), 2015)
Canada has made a wide range of commitments to the promotion of gender equality in development assistance programming. However, in its fragile states programs, these commitments have in fact promoted gender essentialism, treating women as victims of violence rather than as active agents of peace and development. Drawing on a comparative analysis of the National Action Plan on Women, Peace and Security arising from the passing of Security Council Resolution 1325 (2000) and on interviews conducted with a small sample of current and former Canadian government officials, this article documents and analyzes Canada's comparatively weak and limited efforts to promote gender equality abroad under the Harper Conservatives, particularly for fragile and conflict-affected states. The research presented here is situated within broader feminist critiques of international relations and Canadian foreign policy, which document the centrality of gender equality to security and the role that international and national policies play in shaping gendered security dynamics.